Lower Back Pain as an Occupational Hazard Among Ugandan Health Workers - Aleku, Michael; Nelson, Kevin; Abio, Anne; Lowery Wilson, Michael; Lule, Herman (Frontiers in Public Health, 2021)
Lower back pain (LBP) is a public health concern affecting 70-85% of the world’s population. There is paucity of published data on the prevalence, disability and risk factors for LBP among health workers in Uganda. Cross-sectional descriptive study of 245 consecutive participants conducted during February-April 2020. We stratified risks as individual or work related and analysed the data using IBM SPSS version 25. Chi-square was used to measure the significance of association between categorical variables at 95% confidence interval, regarding a p-value of ≤ 0.05 as significant. Results: The mean age of participants was 40.87 years +- 8.74 (SD), with female predominance (69.8%). Majority were either general nurses or midwives (64.9%) and more than half had practiced for over 6-10 years. The prevalence of LBP was 39.6% (n=97). Individual factors associated with LBP were; cigarette smoking (X2=33.040; P=<0.001), alcohol consumption (X2=13.581; P=<0.001), age (X2=14.717; P=0.002), and female gender (X2=4.802; P=0.028). The work related factors significantly associated with LBP were: being a nurse/midwife (X2=9.829; P=0.007), working in the outpatient department (X2=49.752; P=<0.001), bending (X2=43.912; P=<0.001), lifting (X2=33.279; P<0.001), over standing (X2=40.096; P=<0.001), being in awkward positions (X2=15.607; P=<0.001), and pushing patients (X2=21.999; P=<0.001). The prevalence of LBP was high amongst health workers and the main risks were preventable. Health workers should strike a balance between caring for their personal back-health and meeting clients’ needs while manually handling patients. Ergonomic structuring, job organization, back health care courses and use of assistive equipment could reduce such occupational hazards in our low resourced settings.